Reading Comprehension Teaching Strategy Using Questioning The Author (QTA) - Agusti Fransisca; Dewi Syafitri; Ardayati Ardayati (EDULIA: English Education, Linguistic and Art Journal, 2020)
The purpose of this study was to determine the effectiveness of teaching reading comprehension using the Questioning The Author (QTA) strategy. The method used in this research is pre-experimental method. The subjects of this study were all students of class X SMK Pertanian Negeri 2 Tugumulyo. The results showed that: (1) the student’s scores in the pre-test were 57.96; (2) the student’s post-test score was 75.93; (3) paired t-test was 5.17, higher than 1.69 out of 32 with a significant level of 95% as a one-way critical value. In conclusion, learning to read comprehension using the QTA strategy is significantly effective in class X students of SMK Pertanian Negeri 2 Tugumulyo in the 2018/2019 Academic Year. Keywords: Pre-Experimental Research, Questioning The Author Strategy, Teaching Reading Comprehension